Human Vestibulo-Ocular Reflex Adaptation Training: Time Beats Quantity - Muntaseer Mahfuz, M.; Schubert, Michael C.; Figtree, William V. C.; Todd, Christopher J.; Migliaccio, Americo A. (Journal of the Association for Research in Otolaryngology, 2018)
The vestibulo-ocular reflex (VOR) is the main gaze stabilising system during rapid head movements. The VOR is highly plastic and its gain (eye/head velocity) can be increased via training that induces an incrementally increasing retinal image slip error signal to drive VOR adaptation. Using the unilateral incremental VOR adaptation technique and horizontal active head impulses as the vestibular stimulus, we sought to determine the factors important for VOR adaptation including: the total training time, ratio and number of head impulses to each side (adapting and non-adapting sides; the adapting side was pseudo-randomised left or right) and exposure time to the visual target during each head impulse. We tested 11 normal subjects, each over 5 separate sessions and training protocols. The basic training protocol (protocol one) consisted of unilateral incremental VOR adaptation training lasting 15 min with the ratio of head impulses to each side 1:1. Each protocol varied from the basic. For protocol two, the ratio of impulses were in favour of the adapting side by 2:1. For protocol three, all head impulses were towards the adapting side and the training only lasted 7.5 min. For protocol four, all impulses were towards the adapting side and lasted 15 min. For protocol five, all head impulses were to the adapting side and the exposure time to the visual target during each impulse was doubled. We measured the active and passive VOR gains before and after the training. Albeit with small sample size, our data suggest that the total training time and the visual target exposure time for each head impulse affected adaptation, whereas the total number and repetition rate of head impulses did not. These data have implications for vestibular rehabilitation, suggesting that quality and duration of VOR adaptation exercises are more important than rapid repetition of exercises.